TLE4 Is a Critical Mediator of Osteoblast and Runx2-Dependent Bone Development - Shin, Thomas H.; Theodorou, Evangelos; Holland, Carl; Yamin, Rae’e; Raggio, Cathleen L.; Giampietro, Philip F.; Sweetser, David A. (Frontiers in Cell and Developmental Biology, 2021)
Healthy bone homeostasis hinges upon a delicate balance and regulation of multiple processes that contribute to bone development and metabolism. While examining hematopoietic regulation by Tle4, we have uncovered a previously unappreciated role of Tle4 on bone calcification using a novel Tle4 null mouse model. Given the significance of osteoblasts in both hematopoiesis and bone development, this study investigated how loss of Tle4 affects osteoblast function. We used dynamic bone formation parameters and microCT to characterize the adverse effects of Tle4 loss on bone development. We further demonstrated loss of Tle4 impacts expression of several key osteoblastogenic genes, including Runx2, Oc, and Ap, pointing towards a potential novel mechanism for Tle4-dependent regulation of mammalian bone development in collaboration with the RUNX family members.